2019
DOI: 10.1007/s40121-019-0256-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Serological Response to 13-Valent Pneumococcal Conjugate Vaccine Versus 23-Valent Polysaccharide Vaccine in HIV-Infected Adults

Abstract: Introduction Long-term comparative immunologic response to 13-valent pneumococcal conjugate vaccine (PCV13) versus 23-valent polysaccharide vaccine (PPV23) among HIV-infected adults has not yet been investigated. Methods In this prospective pilot study, we quantified in HIV-positive adults serotype-specific IgG concentrations of the 12 pneumococcal serotypes shared by both vaccines 5 years after vaccination with two doses of PCV13 8 weeks apart (group 1) or one dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…For PCV, results varied in two available studies. In the first study, SCRs dropped from to 22% to 4.8% [24] while in the second study high SCRs and SPRs persisted five years after initial vaccination; with a slight advantage for the group that received two PCV vaccinations instead of one (SCR 76% versus 62%) [46] . Of note, this study reported much higher initial SCRs compared to the first study.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…For PCV, results varied in two available studies. In the first study, SCRs dropped from to 22% to 4.8% [24] while in the second study high SCRs and SPRs persisted five years after initial vaccination; with a slight advantage for the group that received two PCV vaccinations instead of one (SCR 76% versus 62%) [46] . Of note, this study reported much higher initial SCRs compared to the first study.…”
Section: Resultsmentioning
confidence: 92%
“…Most studies (27/39) were cohort studies [5 , 13 . [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , 11/39 studies were RCTs [14 , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , and one study was a combination a cohort study and an RCT [57] . Only 8/39 studies included a HIV negative reference group [27 , 29 , 31 , 34 , [38] , [39] , [40] , 48] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations